The Implications of Indonesia’s Public Diplomacy as Host of the G20 Presidency for Domestic Economic Development - Aisyah, Siti; Tyas, Intan Kinanthi Damarin (Padjadjaran Journal of International Relations, 2026)
Indonesia’s G20 Presidency carried the theme Recover Together, Recover Stronger to promote post-pandemic economic recovery. Centered in Bali, the presidency utilized public diplomacy through cultural and tourism-based initiatives. Bali was strategically chosen for its global tourism appeal, allowing Indonesia to showcase its cultural assets as instruments of public diplomacy. This approach positively impacted the local economy, particularly through increased international visitation. This study examines the implementation of Indonesia’s public diplomacy strategies during its G20 Presidency and their implications for national economic development. Framed by Public Diplomacy theory and the concept of Economic Growth, the research employs a qualitative methodology with a descriptive approach to analyse the integration of cultural elements in diplomatic practices and their economic impacts. The findings indicate that Indonesia’s public diplomacy contributed significantly to the growth of key sectors, including tourism, the creative economy, and bilateral cooperation. These results underscore the dual role of public diplomacy in both advancing soft power and generating tangible economic benefits at the domestic level. Presidensi G20 Indonesia mengusung tema Recover Together, Recover Stronger sebagai upaya mendorong pemulihan ekonomi pascapandemi. Berpusat di Bali, presidensi ini memanfaatkan diplomasi publik melalui inisiatif berbasis budaya dan pariwisata. Bali dipilih secara strategis karena daya tarik globalnya, memungkinkan Indonesia untuk memanfaatkan aset budaya sebagai instrumen diplomasi publik. Strategi ini berdampak positif terhadap perekonomian lokal, khususnya melalui peningkatan kunjungan internasional. Penelitian ini bertujuan untuk mengkaji implementasi strategi diplomasi publik Indonesia selama Presidensi G20 serta implikasinya terhadap pembangunan ekonomi nasional. Berlandaskan teori Diplomasi Publik dan konsep Pertumbuhan Ekonomi, penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif untuk menganalisis integrasi elemen budaya dalam praktik diplomasi dan dampaknya terhadap sektor ekonomi. Hasil penelitian menunjukkan bahwa diplomasi publik Indonesia berkontribusi signifikan terhadap perkembangan sektor-sektor utama seperti pariwisata, ekonomi kreatif, dan kerja sama bilateral. Temuan ini menegaskan peran ganda diplomasi publik dalam memperkuat soft power sekaligus menghasilkan manfaat ekonomi yang nyata di tingkat domestik.